Sex Differences in Stress Response: Classical Mechanisms and Beyond - Hodes, G. E.; Bangasser, D.; Sotiropoulos, I; Kokras, N; Dalla, C (Curr Neuropharmacol, 2024)
Neuropsychiatric disorders, which are associated with stress hormone dysregulation, occur at different rates in men and women. Moreover, nowadays, preclinical and clinical evidence demonstrates that sex and gender can lead to differences in stress responses that predispose males and females to different expressions of similar pathologies. In this curated review, we focus on what is known about sex differences in classic mechanisms of stress response, such as glucocorticoid hormones and corticotrophin-releasing factor (CRF), which are components of the hypothalamicpituitary- adrenal (HPA) axis. Then, we present sex differences in neurotransmitter levels, such as serotonin, dopamine, glutamate and GABA, as well as indices of neurodegeneration, such as amyloid β and Tau. Gonadal hormone effects, such as estrogens and testosterone, are also discussed throughout the review. We also review in detail preclinical data investigating sex differences caused by recentlyrecognized regulators of stress and disease, such as the immune system, genetic and epigenetic mechanisms, as well neurosteroids. Finally, we discuss how understanding sex differences in stress responses, as well as in pharmacology, can be leveraged into novel, more efficacious therapeutics for all. Based on the supporting evidence, it is obvious that incorporating sex as a biological variable into preclinical research is imperative for the understanding and treatment of stress-related neuropsychiatric disorders, such as depression, anxiety and Alzheimer's disease.
Keywords: *Amyloid beta-Peptides/metabolism; *Sex Characteristics; antidepressants; Corticotropin-Releasing Hormone/metabolism; Female; glucocorticoids.; Hormones/metabolism; HPA axis; Humans; Hypothalamo-Hypophyseal System/metabolism; Immune; Male; Neurodegeneration; Pituitary-Adrenal System/metabolism; Sex differences; stress; Stress, Psychological/metabolism